Correlation of Serum FGF23 and Chronic Kidney Disease-Mineral and Bone Abnormality Markers With Cardiac Structure Changes in Maintenance Hemodialysis Patients. (8th April 2023) - Zeng, Dewang; Zha, Aiyun; Lei, Ying; Yu, Zongchao; Cao, Rui; Li, Ling; Song, Zhuoheng; Li, Weilong; Li, Yunyi; Liu, Haiping; Huang, Shaoxing; Dong, Xiangnan; et al.
Abstract : Background . CKD-MBD is a mineral and bone metabolism syndrome caused by chronic kidney disease. FGF23 is an important factor regulating phosphorus and is the main influencer in the CKD-MBD process. In this study, we observed the correlation among serum FGF23 and calcium, phosphorus and parathyroid hormone, and the correlation between FGF23 levels and cardiac structural changes in MHD patients. Methods . We examined serum FGF23 concentrations in 107 cases of MHD patients using the ELISA method, recorded demographic information and biochemical data, and analyzed the correlation between serum FGF23 levels and blood calcium and blood phosphorus and PTH levels. All patients were evaluated by cardiac color ultrasound, and we finally analyzed the association between the FGF23 level and cardiac structural changes. Results . In 107 cases of MHD patients, serum FGF23 levels were linearly associated with serum calcium ( r = 0.27 P < 0.01 ) and parathyroid hormone levels ( r = 0.25, P < 0.05 ). FGF 23 was negatively correlated with age ( r = −0.44, P < 0.01 ).Serum FGF23 levels were correlated with right atrial hypertrophy in HD patients (P < 0.05 ). No correlation was found among FGF23, left ventricular hypertrophy/enlargement, and valve calcification stenosis (P > 0.05 ). Conclusion . Serum FGF23 showed a positive correlation among blood calcium levels and PTH levels in hemodialysis patients, and FGF23 levels can affect the incidence of right atrial hypertrophy in MHD patients.